2020
DOI: 10.1007/s13197-020-04443-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine from adlay (Coix lacryma-jobi) biotransformation by Bacillus subtilis and its quality characteristics

Abstract: Adlay, as a traditional Chinese medicine, has been used in nourishing foods, which are rich in a variety of nutrients (special biological compounds). The study was designed to optimize the fermentation parameters of dehulled, polished and broken adlay fermented by Bacillus subtilis BJ3-2 with regard to tetramethylpyrazine (TMP) yield and fibrinolytic enzyme activity. Then the proximate and bioactive components of B. subtilis-fermented adlay were evaluated. Box-Behnken design results showed that the TMP yield w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The culture and collection of Bacillus subtilis BJ3-2 as previously described [29,30]. Briefly, the BJ3-2 strains were cultured overnight in solid LB (Luria-Bertani) at 37 °C, after which a single colony on the plate was picked and cultured again under previously described conditions.…”
Section: The Culture and Collection Of Bacillus Subtilis Bj3-2mentioning
confidence: 99%
“…The culture and collection of Bacillus subtilis BJ3-2 as previously described [29,30]. Briefly, the BJ3-2 strains were cultured overnight in solid LB (Luria-Bertani) at 37 °C, after which a single colony on the plate was picked and cultured again under previously described conditions.…”
Section: The Culture and Collection Of Bacillus Subtilis Bj3-2mentioning
confidence: 99%
“…B. subtilis -fermented dehulled adlay (BDA) was prepared according to the previous method by Wen et al [ 13 ]. Approximately 30 g of dehulled adlay were washed and soaked overnight in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Bacillus -fermented adlay dramatically improved the antioxidant status, lipid metabolism, and intestinal microflora in hyperlipidemic hamsters, indicating that B. subtilis -fermented adlay could be used as a functional food for cardiovascular and intestinal health [ 10 ]. In previous studies, we also found that B. subtilis -fermented dehulled adlay (BDA) contained high levels of tetramethylpyrazine (TMP), phenolics, flavonoids, γ-aminobutyric acid (GABA), and triterpenoids, and exhibited strong antioxidant activity of alcoholic extract [ 11 , 12 , 13 ]. Therefore, it is necessary to further investigate whether the anti-proliferative activity of adlay is improved after fermentation by B. subtilis .…”
Section: Introductionmentioning
confidence: 99%
“…There are higher tetramethylpyrazine, fibrinolytic enzymes, and functional ingredients (phenolics, GABA, triterpenes, flavonoids, and coixenolide) in fermented adlay products, making them more suitable for human consumption [ 30 ]. The compound structures [9-hydroxy-(10 E )-octadecenoic acid, 13-hydroxy-(9 E ,11 E )- octadecadienoic acid, 9-hydroxy-(10 E ,12 E )-octadecadienoic acid(9- E , E -HODE), 10- hydroxy-(8 E )-octadecenoic acid, 8-hydroxy-(9 E )-octadecenoic acid, 11-hydroxy-(9 Z )- octadecenoic acid,9- E , E -HODE] from adlay seed extracts with acetone and 70% ethanol can act as peroxisome proliferator-activated receptor gamma agonists [ 31 ].…”
Section: Functional Ingredients In Adlaymentioning
confidence: 99%